Dry heat and microwave-generated steam protocols for the rapid decontamination of respiratory personal protective equipment in response to COVID-19-related shortages. Issue 1 (September 2020) - Pascoe, M.J.; Robertson, A.; Crayford, A.; Durand, E.; Steer, J.; Castelli, A.; Wesgate, R.; Evans, S.L.; Porch, A.; Maillard, J-Y.
Summary: Background: In the wake of the SARS-CoV-2 pandemic and unprecedented global demand, clinicians are struggling to source adequate access to personal protective equipment. Respirators can be in short supply, though are necessary to protect workers from SARS-CoV-2 exposure. Rapid decontamination and reuse of respirators may provide relief for the strained procurement situation. Method: In this study, we investigated the suitability of 70°C dry heat and microwave-generated steam (MGS) for reprocessing of FFP2/N95-type respirators, and Type-II surgical face masks. Staphylococcus aureus was used as a surrogate as it is less susceptible than enveloped viruses to chemical and physical processes. Results: We observed >4 log10 reductions in the viability of dry S. aureus treated by dry heat for 90 min at 70°C and >6 log10 reductions by MGS for 90 s. After 3 reprocessing cycles, neither process was found to negatively impact the bacterial or NaCl filtration efficiency of the respirators that were tested. However, MGS was incompatible with Type-II surgical masks tested, as we confirmed that bacterial filtration capacity was completely lost following reprocessing. MGS was observed to be incompatible with some respirator types due to arcing observed around some types of metal nose clips and by loss of adhesion of clips to the mask. Conclusion: Considering the advantages and disadvantages of each approach, we propose a reprocessing personal protective equipment/face mask workflow for use in medical areas.